"ST-elevation myocardial infarction associated with air pollution levels in Mexico City". (August 2021) - Lozano-Sabido, E.D.; Berrios-Barcenas, E.A.; Cazares-Diazleal, A.C.; Viveros-Renterìa, E.; Àlvarez-Mosquera, J.B.; Portos-Silva, J.M.; Kiamco-Castillo, C.R.
Abstract: Background Coronary heart disease has multiple risk factors, including air pollution. Numerous pathophysiological mechanisms have been identified with increasing levels of air pollution, mainly with ozone (O3), nitrogen dioxide (NO2), sulphur dioxide (SO2), particulate matter (PM10), fine particulate matter (PM2.5) and carbon monoxide (CO). In Mexico, the pollution level is reported using an air quality index called IMECA. Methods All patients with STEMI admitted at Hospital Español were collected between 2012 and 2019 (N = 348). We conducted a retrospective analysis using the air pollution exposure at the time of each event (lag0), the previous 24 h (lag1), 48 h (lag2), 72 h (lag3) and 5-day cumulative lag. The level of air pollution was analyzed independently using IMECA and particle concentrations. The data was divided in two groups: days with one of more STEMI's (MI group) and days free of events (Control group), using ANCOVA to evaluate the difference between means of both groups taking into account confounders. Results: For days with one or more cardiovascular event, a significant increase in SO2 was observed at lag1; similar increase was found in CO, PM2.5, SO2 at lag2. For the 5-day cumulative lag, SO2 and PM2.5 showed a significant increase. No differences were found using the IMECA levels in both groups. Conclusions: The elevated concentrations levels of CO, SO2 and PM2.5 showed significant association with STEMI at different time points before the event. Ozone, PM10 and NO2 showed no difference between groups. IMECA levels showed no association with STEMI in our study.